East India Company at Home, 1757-1857 - Smith, Kate, 1981-; Finn, Margot C. (Book collections on Project MUSE., 2018)
The East India Company at Home, 1757-1857 explores how empire in Asia shaped British country houses, their interiors and the lives of their residents. It includes chapters from researchers based in a wide range of settings such as archives and libraries, museums, heritage organisations, the community of family historians and universities. It moves beyond conventional academic narratives and makes an important contribution to ongoing debates around how empire impacted Britain.